The Examination on Satisfaction and Behavioral Intention of Natural Science Majors Students Toward E-learning in Sichuan, China - Zhao, Yi; Inthawadee, Sutthisak; Suesaowaluk, Poonphone (Scholar: Human Sciences, 2024)
Purpose: This paper mainly studies the factors impacting natural science majors’ satisfaction and behavioral intention to adopt electronic learning (E-learning) at a public university in Sichuan, China. A conceptual framework was built upon the relationship between system quality, satisfaction, performance expectancy, effort expectancy, social influence, attitude, and behavioral intention. Research design, data, and methodology: The sample is 500 natural science major’s undergraduates from a public university in Sichuan Province. Non-probability samplings include purposive sampling, quota sampling, and convenient sampling. The validity and reliability test were employed before the data collection, approved by the item-objective congruence (IOC) index Cronbach’s Alpha coefficient values of the pilot test. The data were analyzed by Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). Results: Research shows that all hypotheses were consistent with the research objectives. System quality, performance expectancy, effort expectancy, social influence, and attitude significantly impact behavioral intention. Satisfaction has the strongest impact on natural science major students’ behavioral intention to use E-learning Conclusions: Based on the findings, higher education decision-makers and policymakers focus on enhancing student satisfaction with e-learning by strengthening the IT infrastructure and their ability to sustain remote learning services.